Homonymy and the Cognitive Operator of Norm in German - Kiyko, Svitlana; Kiyko, Yuriy (East European journal of psycholinguistics, 2020)
The works of many linguists view homonymy as a negative phenomenon, which interferes with communication, complicates the perception of information, and decreases the effectiveness of the language as a means of communication. At the same time homonymy is a positive phenomenon which contributes to the compactness of the language, and allows to economize the units of the plain of content. The objective of our research is to determine the factors that differentiate the meaning of homonymic units, based on the broad factual material and psycholinguistic experiments. The components of intralinguistic homonymic rows based on the category of markedness, which correlates with the cognitive operator of norm / deviation. Among the criteria of markedness for homonymic differentiation are areal, social, chronological, and stylistic. The fact that one of the elements of the homonymic row is unmarked was proved by a number of psycholinguistic experiments, where we offered the German speakers to suggest the first association word which occurred to them referring the homonyms in the list. The experiment was carried out in a group of students from the Institute of German Studies, Technical University Chemnitz (Germany), aged 21-25, whose native language is German. The psycholinguistic analysis shows that 97 per cent of homonymic pairs have both marked and unmarked components. This allows to explain homonymy from the point of view of the correlation of “markedness/unmarkedness”, and wider – “norm/deviation”. From the cognitive point of view language markedness is derived from cognitive markedness, i.e. the unmarked language meaning corresponds to the cognitively normal (natural, expected) state of things, and the marked language meaning corresponds to cognitive deviation, i.e. unnatural, unexpected state of things. Normal state of things belongs to the cognitive image of human experience, and is conceptualized with the minimal mental calculating effort, i.e. is activated automatically; and deviations from this image require additional calculating resources for their activation. Thus, language markedness reflects cognitive operators of norm/deviation in the specific language means in language structures, including homonymic pairs and homonymic rows. References Bridges, R.S. (2004). On English Homophones. Society for Pure English Tract 02. Oxford: Clarendon Pr. Retrieved from: http://www.gutenberg.org/files/14227/14227-h/14227-h.htm (01.05.2020) Cairns, H.S. (1973). Effects of bias on processing and reprocessing of lexically ambiguous sentences. Journal of Experimental Psychology, 97, 337-343. Croft, W. (2003). Typology and universals. 2-d ed. Cambridge: Cambridge University Press. Ducháček, O. (1953). O vzájemném vlivu tvaru a významu slov. Praha: Státní pedagogické nakladatelství. Ferreira, L. (2010). Metaphor comprehension in foreign language. In L. Scliar-Cabral, (Ed). Psycholinguistics: Scientific and Technological Challenges. (pp. 84-98). Porto Alegre: EDIPUCRS, Foss, D.J. & Jenkins C.M. (1973). Some effects of context on the comprehension of ambiguous sentences. Journal of Verbal Learning and Verbal Behavior, 12, 577-589. Greenberg, J. (1966). Language universals, with special reference to feature hierarchies. The Hague: Mouton. Hogaboam, T.W. & Perfetti, C.A. (1975). Lexical ambiguity and sentence comprehension. Journal of Verbal Learning and Verbal Behaviour, 14, 265-274. Кибрик, А.Е. (2008). Лингвистическая реконструкция когнитивной структуры. Вопросы языкознания. 4, 51-77. Кійко, С.В. (2016). Синергетика омонімії як мовного, мовленнєвого і міжмовного явища. Чернівці: Родовід. Mаулер, Ф.И. (1983). Грамматическая омонимия в современном английском языке. Ростов: Изд. Рост. университета. Новиков, Л.А. (1982). Семантика русского языка. М.: Высшая Школа. Реформатский, А.А. (2004). Введение в языкознание. 5 изд. М.: Аспект Пресс Press. Ruoff, A. (2014). Häufigkeitswörterbuch gesprochener Sprache. 2. Auflage. Berlin: de Gruyter. Reprint 2014. DOI: https://doi.org/10.1515/9783110916058 References (translated and transliterated) Bridges, R.S. (2004). On English Homophones. Society for Pure English Tract 02. Oxford: Clarendon Pr. Retrieved from: http://www.gutenberg.org/files/14227/14227-h/14227-h.htm (01.05.2020) Cairns, H.S. (1973). Effects of bias on processing and reprocessing of lexically ambiguous sentences. Journal of Experimental Psychology, 97, 337-343. Croft, W. (2003). Typology and universals. 2-d ed. Cambridge: Cambridge University Press. Ducháček, O. (1953). O vzájemném vlivu tvaru a významu slov. Praha: Státní pedagogické nakladatelství. Ferreira, L. (2010). Metaphor comprehension in foreign language. In L. Scliar-Cabral, (Ed). Psycholinguistics: Scientific and Technological Challenges. (pp. 84-98). Porto Alegre: EDIPUCRS. Foss, D.J. & Jenkins C.M. (1973). Some effects of context on the comprehension of ambiguous sentences. Journal of Verbal Learning and Verbal Behavior, 12, 577-589. Greenberg, J. (1966). Language universals, with special reference to feature hierarchies. The Hague: Mouton. Hogaboam, T.W. & Perfetti, C.A. (1975). Lexical ambiguity and sentence comprehension. Journal of Verbal Learning and Verbal Behaviour, 14, 265-274. Kibrik, А.Е. (2008). Lingvističeskaya rekonstrukciya kognitivnoy struktury [Linguistic reconstruction of cognitive structure]. Voprosy yazykoznaniya, 4, 51–77. Kiyko, S.V. (2016). Synergetyka omonimii yak movnoho, movlennevoho i moshmovnoho yavyshcha. [Synergy of homonymy as language, speech and interlanguage phenomenon]. Chernivtsi: Rodovid. Mauler, F.I. (1983). Grammatičeskaya omonimiya v sovremennom angliyskom yazyke [Grammatical homonymy in Modern English]. Rostov: Rostov University Publishers. Novikov, L.А. (1982). Semantika russkogo yazyka [Semantics of Russian language]. М.: Vys. shkola. Reformatskiy, А.А. (2004). Vvedeniye v yazykoznaniye [Introduction into linguistics]. 5-th ed. Мoscow: Aspekt Press. Ruoff, A. (2014). Häufigkeitswörterbuch gesprochener Sprache. 2. Auflage. Berlin: de Gruyter. Reprint. https://doi.org/10.1515/9783110916058.